2009
DOI: 10.1103/physrevlett.102.110502
|View full text |Cite
|
Sign up to set email alerts
|

Restrictions on Transversal Encoded Quantum Gate Sets

Abstract: Transversal gates play an important role in the theory of fault-tolerant quantum computation due to their simplicity and robustness to noise. By definition, transversal operators do not couple physical subsystems within the same code block. Consequently, such operators do not spread errors within code blocks and are, therefore, fault tolerant. Nonetheless, other methods of ensuring fault tolerance are required, as it is invariably the case that some encoded gates cannot be implemented transversally. This obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
369
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(375 citation statements)
references
References 9 publications
5
369
0
1
Order By: Relevance
“…Moreover, this result is restricted to models that give rise to fault-tolerant quantum computation by transversal gates. Indeed, quantum coding theory has shown that universal transversal operations are known to be incompatible with stabilizer error correction (Eastin and Knill, 2009;Zeng, Cross, and Chuang, 2011; Anderson and Jochym-O'Connor, 2014). The reader may question this remark as to how the six-dimensional color code achieves a universal set of operations given known restrictions on universal transversal gate sets.…”
Section: Thermally Stable Quantum Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this result is restricted to models that give rise to fault-tolerant quantum computation by transversal gates. Indeed, quantum coding theory has shown that universal transversal operations are known to be incompatible with stabilizer error correction (Eastin and Knill, 2009;Zeng, Cross, and Chuang, 2011; Anderson and Jochym-O'Connor, 2014). The reader may question this remark as to how the six-dimensional color code achieves a universal set of operations given known restrictions on universal transversal gate sets.…”
Section: Thermally Stable Quantum Computationmentioning
confidence: 99%
“…As an aside remark, the nontrivial braiding statistics between anyons can be obtained from the commutation relations of logical operators (Einarsson, 1990) The ground space of the toric code is naturally described with a basis labeled by anyonic charges a, wrapping around a nontrivial cycle of the torus and then annihilating with its antiparticle, such as that shown in red. (b) Two anyonic excitations created that can propagate at no energy cost to affect the ground space of the system.…”
Section: E Topological Order and Anyons In The Toric Codementioning
confidence: 99%
“…Classification of fault-tolerant implementable logical gates in topological quantum error-correcting codes is an important stepping stone toward far-reaching goal of universal quantum computation [1][2][3][4]. Characterization of logical operators is also essential in understanding braiding and fusion rules of anyonic excitations arising in topologically ordered systems [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Stabilizer codes only allow coherent implementation of a limited group of fault tolerant gates, the so-called transversal gates. Unfortunately, recent research has shown that no stabilizer code can both protect against generic errors and offer a universal set of transversal gates [5]. Similarly, topologically protected groups of gates, implemented by braiding anyons, are not universal for many species of anyons [6][7][8].…”
mentioning
confidence: 99%